2017
DOI: 10.1136/archdischild-2017-313190
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive high-frequency oscillatory ventilation in preterm infants: a randomised controlled cross-over trial

Abstract: DRKS00007171, results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 15 publications
(15 reference statements)
3
31
0
2
Order By: Relevance
“…Another randomized crossover trial did not demonstrate an increased efficacy of nHFOV compared with nCPAP for CO 2 clearance in premature infants. Moreover the Authors found a high failure rate for nHFOV as noninvasive respiratory support . Nevertheless, significant differences exist between this latter study and our experience: a) the age at enrolment: the first week of life vs three weeks of life; b) the machine used to generate nHFOV: different neonatal ventilators (Sophie, Stephan, Gaggenbach, Germany, and Leoni plus, Heinen + Lowenstein, Bad Ems, Germany) versus just one ventilator able to deliver noninvasive respiratory modes only (CNO Medin, Germany) and producing high‐frequency oscillation by flow interruption with cyclic opening‐closure of the end expiratory valve; c) the interface adopted in the studied patients: bi‐nasal prongs or nasal masks versus only bi‐nasal prongs of right size; and d) the modality of obtaining the primary outcome (pCO 2 behavior): through arterial or arterialized blood gas analysis versus TcCO 2 data.…”
Section: Discussionmentioning
confidence: 61%
“…Another randomized crossover trial did not demonstrate an increased efficacy of nHFOV compared with nCPAP for CO 2 clearance in premature infants. Moreover the Authors found a high failure rate for nHFOV as noninvasive respiratory support . Nevertheless, significant differences exist between this latter study and our experience: a) the age at enrolment: the first week of life vs three weeks of life; b) the machine used to generate nHFOV: different neonatal ventilators (Sophie, Stephan, Gaggenbach, Germany, and Leoni plus, Heinen + Lowenstein, Bad Ems, Germany) versus just one ventilator able to deliver noninvasive respiratory modes only (CNO Medin, Germany) and producing high‐frequency oscillation by flow interruption with cyclic opening‐closure of the end expiratory valve; c) the interface adopted in the studied patients: bi‐nasal prongs or nasal masks versus only bi‐nasal prongs of right size; and d) the modality of obtaining the primary outcome (pCO 2 behavior): through arterial or arterialized blood gas analysis versus TcCO 2 data.…”
Section: Discussionmentioning
confidence: 61%
“…There is insufficient evidence to recommend NIPPV as primary mode of respiratory support in the delivery room. Nasal interfaces have also been used with high frequency oscillatory ventilation (HFOV), but results have been inconclusive [99, 100]. …”
Section: Non-invasive Respiratory Supportmentioning
confidence: 99%
“…10,16,19,22 Therefore, the nHFO mode provides not only rescue therapy, but nHFO with face mask interface is the choice of NIV to prevent extubation failure (prophylactic therapy) in neonates. The present cohort (78 neonates) is larger than any previous report on neonatal nHFO (3, 19 13, 13 15, 12 16, 16 20, 23 21, 10,14 37, 22 and 63 15 neonates), especially reintubation as the primary outcome. 10,19,23 The reintubation rates of the nHFO group on days 3 and 7 from our study were 12.8 and 15.4%, respectively.…”
Section: Discussionmentioning
confidence: 71%
“…12 In contrast to another RCT, no difference of CO 2 clearance was shown between nHFO and nCPAP in very preterm neonates. 13 We performed a retrospective cohort study of neonates admitted to the NICU at Songklanagarind Hospital from 2013 to 2017. This study aimed to compare the endotracheal reintubation rates between the nHFO and nCPAP groups who were followed up for up to 7 days.…”
mentioning
confidence: 99%